Secondary Imaging Findings Aid in Prenatal Diagnosis and Characterization of Congenital Diaphragmatic Hernia: Role of an Abnormal Orientation of Vascular Structures and Gallbladder Position. (23rd September 2018) - Didier, Ryne A.; DeBari, Suzanne E.; Oliver, Edward R.; Gebb, Juliana S.; Howell, Lori J.; Hedrick, Holly L.; Adzick, N. Scott; Coleman, Beverly G.
Abstract : Objectives: To determine whether an abnormal orientation of the abdominal or hepatic vasculature and an abnormal gallbladder position on prenatal ultrasound (US) imaging are associated with intrathoracic liver herniation and postnatal outcomes in cases of congenital diaphragmatic hernia (CDH). Methods: Children who underwent prenatal US examinations and postnatal CDH repair at our institution were eligible. Prenatal US images were reviewed, and the orientation of the superior mesenteric artery (SMA) and hepatic veins as well as gallbladder position were recorded. Findings were correlated with prenatal US measurements (lung‐to‐head ratio and calculated observed‐to‐expected lung‐to‐head ratio) and postnatal outcomes, including intrathoracic liver herniation, an extracorporeal membrane oxygenation (ECMO) requirement, and mortality. Results: A total of 175 patients met inclusion criteria. The SMA was shown in 168 cases and had a cephalad orientation in 95.4% (161 of 168), which was not associated with outcome measures and represented bowel herniation. A cephalad orientation of the hepatic veins was identified in 52.6% (90 of 171) and was associated with intrathoracic liver herniation, an ECMO requirement, and mortality ( P  < .01). In right‐sided CDH, the gallbladder was intrathoracic in 91.3% (21 of 23). In left‐sided CDH, an abnormal gallbladder position was seen in 51.3% (76/152) and was associated with intrathoracic liver herniation, an ECMO requirement, mortality, and lower lung‐to‐head ratio and observed‐to‐expected lung‐to‐head ratio values. When combined, abnormal hepatic vein and gallbladder positions showed good sensitivity and specificity in predicting intrathoracic liver herniation (area under the curve, 0.93). Conclusions: Abnormal SMA, hepatic vein, and gallbladder positions can be used to improve prenatal characterization of CDH. Accurate depiction of these structures on prenatal US images may aid in patient counseling and postnatal management.